Light Scattering Reviews 3 - Kokhanovsky, Alexander A.; SpringerLINK eBooks - English/International Collection (2008). (New York Springer, 2008)
Annotation This is the 3rd volume of a "Light Scattering Reviews" series devoted to current knowledge of light scattering problems and both experimental and theoretical research techniques related to their solution. This volume covers applications in remote sensing, inverse problems and geophysics, with a particular focus on terrestrial clouds. The influence of clouds on climate is poorly understood. The theoretical aspects of this problem constitute the main emphasis of this work.
Scholarly & Professional
Keywords: Electronic books